2021
DOI: 10.1097/yco.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Addressing psychological resilience during the coronavirus disease 2019 pandemic: a rapid review

Abstract: Purpose of review The mental health toll on populations exposed to COVID-19 is alarming, and there is a need to address this with urgency. This current review provides insights on how individuals, communities, and specific populations, such as healthcare workers and patients are leveraging pre-COVID-19 and peri-COVID-19 factors to reinforce their psychological resilience during the global public health crisis. Recent findings Examination of the extant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 37 publications
5
58
0
1
Order By: Relevance
“…Even after experiencing terrible events, the evidence suggests that people may experience some positive aspects, such as in the case of bereavement, rape, cancer, terrorism, natural disasters and even epidemics, as in the case of the MERS outbreak [ 14 , 15 , 16 , 17 ]. The ability to adapt to unpleasant situations and to recover quickly from trauma has been studied through the constructs of resilience, posttraumatic growth (PTG) and coping strategies [ 11 , 12 , 14 , 18 , 19 ]. Research has not yet reached unanimous agreement on the definition and conceptualization of resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after experiencing terrible events, the evidence suggests that people may experience some positive aspects, such as in the case of bereavement, rape, cancer, terrorism, natural disasters and even epidemics, as in the case of the MERS outbreak [ 14 , 15 , 16 , 17 ]. The ability to adapt to unpleasant situations and to recover quickly from trauma has been studied through the constructs of resilience, posttraumatic growth (PTG) and coping strategies [ 11 , 12 , 14 , 18 , 19 ]. Research has not yet reached unanimous agreement on the definition and conceptualization of resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the literature shows that the aftermath of tragic events can have a positive impact in terms of personal growth and meaning, suggesting that resilient attitudes may be more prevalent than expected [ 11 , 12 , 15 , 18 ]. In this regard, Bonanno [ 12 ] challenged the grief work assumption, arguing that the most common reaction to highly traumatic events are not symptoms of distress such as PTSD and depression as much as resilience.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis including longitudinal as well as cross-sectional studies evaluating correlations between resilience and mental health showed that resilience is negatively correlated to negative indicators of mental health, such as depression, anxiety and negative affect, and positively correlated to positive indicators of mental health, such as life satisfaction and positive affect [52]. Further, a review on the role of resilience as a protective factor regarding anxiety, depression and post-traumatic stress during the COVID-19 pandemic revealed that "resilient" coping strategies to deal with COVID-19-related distress are common [53]. However, evidence on the nature of the association of resilience and psychological distress is still inconclusive [54][55][56] and more research is needed to identify effective interventions [53].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a review on the role of resilience as a protective factor regarding anxiety, depression and post-traumatic stress during the COVID-19 pandemic revealed that "resilient" coping strategies to deal with COVID-19-related distress are common [53]. However, evidence on the nature of the association of resilience and psychological distress is still inconclusive [54][55][56] and more research is needed to identify effective interventions [53]. Dorman-Ilan et al [32] found that relatives who did not feel protected by the hospital might suffer from increased anxiety even one month after patients' discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation